L31 The Quality Of Life Of Spanish Patients With Huntington's Disease Measured With H-qol-i And Eq-5d. (17th September 2014) - Hernandez, B; Trigo, P; García de Yebenes, J; Clay, E; Toumi, M
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disorder with wide-ranging effects on motor, cognitive and behavioural effects and a great impact on patient's health- related quality of life (HRQoL). HRQoL measures are increasingly used in clinical assessment to evaluate intervention effectiveness. Such assessments allow decision makers to consider patient and caregiver perspectives. Aims: The aim of the study was to evaluate the HRQoL of Spanish HD patients and to compare results provided by EQ-5D and H-QoL-I instruments. Methods: This was an observational, cross-sectional study conducted in Spain on the burden of disease (BoD) and HRQoL of HD patients and caregivers. HD Patients were recruited through a neurologist in a clinical setting. Several clinical, functional, BoD and HRQoL measures were collected (we present only HRQoL data). The EuroQOL five dimensions questionnaire (EQ-5D) and Huntington Quality of Life Instrument (H-QoL-I: a new validated HD specific HRQoL scale) were voluntarily self-completed. Pearson's correlation tests were computed. Results: 55 patients were recruited. The mean ± SD age was 50 ±14 years. 51% were female. Results from H-QoL-I indicated that the psychological dimension was the most altered dimension, slightly greater than the motor dimension (scores: 58.06 and 56.96 respectively) whereas social dimension was not altered (score 80.93). Usual activities and anxiety/depression were the most altered dimensions based on the EQ-5D whereas pain was the least altered dimension. All Pearson's correlations between the H-QoL-I and EQ-5D were statistically significant (p < 0.01). Conclusion: The quality of life of the Spanish HD patients included in this study was seriously affected by the disease. Motor and psychological dimensions were the most affected whereas pain and social dimensions were less affected. Better therapeutic options to improve motor function, and hence, HRQoL are needed.